Introduction to the site-specific etiologic results from the pneumonia etiology research for child health (PERCH) study - Deloria Knoll, M; Prosperi, C; Baggett, HC; Brooks, WA; Feikin, DR; Hammitt, LL; Howie, SRC; Kotloff, KL; Madhi, SA; Murdoch, DR; Scott, JAG; Thea, DM; et al. (Lippincott, Williams and Wilkins, 2021)
The Pneumonia Etiology Research for Child Health (PERCH) study evaluated the etiology of severe and very severe pneumonia in children hospitalized in 7 African and Asian countries. Here, we summarize the highlights of in-depth site-specific etiology analyses published separately in this issue, including how etiology varies by age, mortality status, malnutrition, severity, HIV status, and more. These site-specific results impart important lessons that can inform disease control policy implications.